Book Review: Essentials of Accessible Grounded Theory (Stern & Porr, 2011) - Odis E. Simmons (Grounded Theory Review: An International Journal)
Although Porr is a relative newcomer to grounded theory, Stern has been at it for many years (she received her PhD under Glaser and Strauss in 1977). She has been instrumental in introducing many students to grounded theory, particularly in the nursing field, as well as making notable contributions to grounded theory literature. As Stern's (1994) observations and insights suggested, constructivist versions of grounded theory emerged and spread in part because grounded theory was often being taught by teachers who themselves had a superficial, distorted understanding of the methodology, because they had learned it "minus mentor." Given her observations, insights, and writings, when I began reading Essentials, my expectations were high. But, after reading it, I concluded that, in some important ways, it falls short. Given Stern's considerable experience and previous contributions to grounded theory, it is ironic that Essentials contains more confusing and subtly inaccurate content than a book written for neophyte grounded theorists should. Although I think it is a noble effort with useful information, it contains material that is at variance with classic grounded theory, yet this isn't made clear to the reader. Because Stern and Porr failed to make a clear distinction between classic and other forms of grounded theory, many readers, particularly neophytes, will of course expect that what they present in this book accurately represents essential canons of all types of grounded theory, including classic. Readers will carry the understandings and misunderstandings gained from the book into their research and discussions with other neophytes and individuals who express interest in grounded theory.